A nanoparticle catalyst, a preparation method and application thereof

CN122687252APending Publication Date: 2026-09-04THE CHINESE UNIV OF HONG KONG (SHENZHEN)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510255339.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-04
Publication Date
2026-09-04

AI Technical Summary

Technical Problem

[0012]本申请针对现有技术中能耗高、效率低和副反应(如析氢反应)难以抑制的问题,提出了一种能够在低电压条件下实现高效率电解水制氢和同时高效生成氨的技术方案

Benefits of technology

[0044] (1) Significantly reduced energy consumption: Traditional water electrolysis requires a voltage of more than 1.5V, while the catalyst of this invention can achieve efficient electroreduction of nitrate to ammonia at a voltage of less than 1.23V.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122687252A_ABST
    Figure CN122687252A_ABST
Patent Text Reader

Abstract

The application discloses a kind of nanoparticle catalyst and its preparation method, application, belong to catalyst field.The chemical formula of the catalyst is MCu4 (M is one of Ir, Pt, Pd), wherein the atomic ratio of noble metal and copper is 1:4.The nanoparticle catalyst is based on MCu4 Alloy nanoparticle catalyst, can realize the direct production of ammonia under the condition of lower theoretical voltage 1.23V.The catalyst has double function, can effectively promote nitrate reduction reaction (NO3RR), and the faraday efficiency in electrolysis process is as high as 93.6%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to a nanoparticle catalyst, its preparation method, and its application, and belongs to the field of catalysts. Background Technology

[0002] With the increasing global demand for ammonia production, green synthesis methods for ammonia, as an important chemical feedstock and energy carrier, have attracted widespread attention. Traditional ammonia synthesis methods mainly rely on the Haber-Bosch process, which requires high temperature and pressure, consumes large amounts of fossil fuels, and causes significant carbon emissions. Therefore, developing efficient and sustainable new ammonia synthesis pathways is of significant practical importance.

[0003] In recent years, the nitrate electroreduction reaction (NO3RR) has gradually become an alternative method for ammonia production. This method utilizes renewable electricity to directly reduce nitrate to ammonia, offering advantages such as mild reaction conditions, low energy consumption, and environmental friendliness. However, catalyst efficiency and selectivity remain the main bottlenecks restricting its industrial application.

[0004] Existing catalysts mainly include noble metal catalysts (such as platinum and iridium) and non-noble metal catalysts (such as nickel and copper), but these catalysts often exhibit high overpotentials and low Faradaic efficiencies during the reaction. Furthermore, catalyst stability and resistance to poisoning are also current research hotspots. Many catalysts may experience performance degradation under prolonged current exposure, leading to reduced ammonia formation efficiency.

[0005] Therefore, developing novel, highly efficient catalysts to improve the catalytic performance of nitrate electroreduction reactions, reduce energy consumption, and enhance Faraday efficiency has become an important research direction. This can not only promote the green synthesis of ammonia but also provide effective technical support for achieving carbon neutrality.

[0006] In existing technologies, various catalysts have been developed, such as platinum, ruthenium, and nickel-based alloys. However, these catalysts typically suffer from the following drawbacks:

[0007] (1) High overpotential: Most existing catalysts require a high overpotential to effectively catalyze the reaction during water electrolysis, resulting in energy loss.

[0008] (2) High cost: Many high-efficiency catalysts (such as platinum and ruthenium) are expensive, which limits their feasibility in large-scale applications.

[0009] (3) Poor selectivity: In applications such as ammonia production, existing catalysts often cannot effectively suppress hydrogen evolution reactions, resulting in poor product selectivity and affecting the ammonia generation efficiency.

[0010] Based on the above situation, developing new and efficient catalysts to reduce the energy consumption and cost of water electrolysis is of great practical significance and urgency. Summary of the Invention

[0011] The technical problem to be solved by this application is:

[0012] This application addresses the problems of high energy consumption, low efficiency, and difficulty in suppressing side reactions (such as hydrogen evolution reaction) in existing technologies by proposing a technical solution that can achieve high-efficiency water electrolysis for hydrogen production and simultaneously generate ammonia efficiently under low voltage conditions.

[0013] The present invention aims to develop a novel bifunctional catalyst that can effectively reduce the reaction overpotential and inhibit the hydrogen evolution reaction during the electrolytic reduction of nitrate, thereby achieving highly selective ammonia generation and efficient hydrogen storage with low energy consumption.

[0014] The catalyst in this application uses IrCu4 alloy nanoparticles, which can effectively catalyze NO3RR under conditions lower than the theoretical voltage of 1.23V, which not only improves the catalytic efficiency but also significantly reduces energy consumption.

[0015] Furthermore, the catalyst of this application exhibits excellent Faraday efficiency in the direct production of ammonia, effectively suppressing competing reactions and thus increasing ammonia yield. The development of this novel catalyst not only provides a new solution for the efficient conversion of hydrogen energy but also lays the foundation for achieving carbon neutrality and promoting the development of a hydrogen economy. Therefore, the development of the technology presented in this application has significant theoretical value and broad application prospects.

[0016] According to a first aspect of this application, a nanoparticle catalyst is provided. The catalyst activity is enhanced by employing IrCu4 alloy nanoparticles and optimizing inter-element electron transfer and structural rearrangement.

[0017] A nanoparticle catalyst, wherein the chemical formula of the catalyst is MCu4; wherein M represents a noble metal, and M is selected from Ir, Pt, and Pd;

[0018] The atomic ratio of precious metals to copper is 1:4.

[0019] Specifically, the catalyst has the chemical formula IrCu4, wherein the atomic ratio of iridium to copper is 1:4.

[0020] Optionally, the catalyst has an alloy structure in which copper atoms partially replace the positions of noble metal atoms in the crystal lattice, forming a uniformly distributed alloy phase;

[0021] The catalyst has a face-centered cubic (FCC) crystal structure.

[0022] The catalyst has an alloy structure, with copper atoms partially replacing the positions of noble metal atoms in the crystal lattice, forming a uniformly distributed alloy phase. Characterization by X-ray diffraction (XRD) and high-resolution transmission electron microscopy (HRTEM) confirmed that it has a face-centered cubic (FCC) crystal structure, with a lattice constant slightly expanded compared to single-metal Cu.

[0023] Optionally, the catalyst has an average particle size of 3 to 3.5 nm.

[0024] According to a second aspect of this application, a method for preparing a nanoparticle catalyst is provided.

[0025] The preparation method of the above-mentioned nanoparticle catalyst includes:

[0026] The noble metal precursor and Cu precursor were dissolved in an oil solvent and heated and stirred to obtain the nanoparticle catalyst.

[0027] Optionally, the noble metal precursor is selected from at least one of iridium acetylacetone (Ir(acac)3), chloroplatinic acid (H2PtCl6), and palladium chloride (PdCl2);

[0028] Optionally, the Cu precursor is selected from at least one of copper acetylacetonate (Cu(acac)2) and copper chloride (CuCl2).

[0029] Optionally, the oil solvent is selected from at least one of oleylamine and octadecene.

[0030] Specifically, the oil solvent is selected from oleylamine.

[0031] Optionally, the molar ratio of the noble metal precursor to the Cu precursor is 1:4.

[0032] Optionally, the ratio of precious metal precursor to oil solvent is 1 mg: 2 to 5 mL.

[0033] Optionally, the heating and stirring conditions are: temperature of 200-300℃, time of 3-8h, and stirring speed of 400-600rpm.

[0034] Optionally, Ir and Cu precursors are mixed in a molar ratio of 1:4 and dissolved in oleylamine to form a uniform green solution; the solution is then heated and stirred in an oil bath to form IrCu4 alloy nanoparticles.

[0035] According to a third aspect of this application, an application of a nanoparticle catalyst is provided.

[0036] The above-described nanoparticle catalyst is used in the electroreduction of nitrate to ammonia. Compared with existing technologies, it features low-voltage operation: in existing technologies, the electroreduction of nitrate to ammonia typically requires a voltage higher than 1.23V, while the catalyst of this invention achieves stable ammonia production under conditions lower than this theoretical voltage; it features bifunctional catalysis: the catalyst of this invention catalyzes NO3RR, which, compared with a single catalyst, can improve the overall reaction efficiency and avoid competing reactions (such as the hydrogen evolution reaction (HER)); it features high Faradaic efficiency: compared with existing catalysts, the Faradaic efficiency of this catalyst is significantly improved, reducing the occurrence of side reactions and ensuring high selectivity and yield of ammonia.

[0037] This nanoparticle catalyst exhibits superior catalytic activity: it demonstrates excellent NO3RR catalytic performance in the reaction. In the nitrate reduction reaction, the catalyst completely inhibits the hydrogen evolution reaction at a positive potential (0V vs. RHE), achieving a Faraday efficiency of up to 93.6%. It also exhibits good stability: under simulated commercial conditions (16cm⁻¹), the catalyst... 2 The flow electrolyzer allows the catalyst to operate stably for 50 hours at a voltage below 1.23V, achieving efficient electrolysis of water and ammonia generation.

[0038] Optionally, the application device for the catalyst includes:

[0039] The catalyst is integrated into the flow electrolyzer as both the cathode and anode materials. The specific parameters of the device are as follows:

[0040] Parameters of the flowing electrolyzer: The electrolyzer area is 16 cm². 2 The membrane electrode assembly (MEA) is used, with IrCu4 catalysts used for both the cathode and anode, and the electrolyte is 1M KOH + 0.1M KNO3.

[0041] Operating conditions: Electrolytic cell at 2mA / cm 2 It operates at current density, achieving efficient ammonia generation and hydrogen storage at voltages below 1.23V.

[0042] The beneficial effects that this application can produce include:

[0043] The nanoparticle catalyst, its preparation method, and its application provided in this application have the following advantages:

[0044] (1) Significantly reduced energy consumption: Traditional water electrolysis requires a voltage of more than 1.5V, while the catalyst of this invention can achieve efficient electroreduction of nitrate to ammonia at a voltage of less than 1.23V.

[0045] (2) Highly selective ammonia generation: By effectively inhibiting the HER reaction and improving the selectivity of NO3RR, the Faraday efficiency of ammonia generation is as high as 93.6%.

[0046] (3) Green and environmentally friendly: Ammonia is generated directly at room temperature and pressure through electrochemical reaction, without the need for high temperature and high pressure and fossil fuel dependence, thus reducing carbon emissions.

[0047] (4) Long-term stability: Under simulated commercial conditions, the catalyst operated stably for 50 hours at low voltage, demonstrating excellent durability.

[0048] The nanoparticle catalyst provided in this application has broad application prospects and can be widely used in:

[0049] (1) Low-energy hydrogen production and storage: Ammonia is directly generated by the reduction of nitrate ions and used in fuel cells or energy transportation.

[0050] (2) Industrial wastewater treatment: Achieve efficient ammonia generation and water purification in low-concentration nitrate solutions (such as industrial wastewater). Attached Figure Description

[0051] Figure 1 The image shows the XRD patterns of the IrCu4 alloy nanoparticle catalyst prepared in Example 1 and Ir and Cu.

[0052] Figure 2 The images show TEM images of the IrCu4 alloy nanoparticle catalyst prepared in Example 1. Image a has a scale of 50 nm, and image b has a scale of 20 nm.

[0053] Figure 3 The image shows the EDS spectrum of the IrCu4 alloy nanoparticle catalyst prepared in Example 1.

[0054] Figure 4 The images show the Ir element 4f energy spectrum of the IrCu4 alloy nanoparticle catalyst and Ir nanoparticles prepared in Example 1.

[0055] Figure 5 The diagram shows the operation of the IrCu4 alloy nanoparticle catalyst prepared in Example 1 under simulated commercial conditions. Detailed Implementation

[0056] The present application is described in detail below with reference to the embodiments, but the present application is not limited to these embodiments.

[0057] Unless otherwise specified, all raw materials used in the embodiments of this application were purchased through commercial channels.

[0058] Unless otherwise specified, all test methods are standard and all instrument settings are those recommended by the manufacturer.

[0059] The analysis method in the embodiments of this application is as follows:

[0060] The Rigaku SmartLab X-ray diffractometer was used for X-ray diffraction (XRD) analysis, the JEOL JEM-2100F microscope was used for transmission electron microscopy (TEM) image capture, the NORAN System7X was used for energy-dispersive X-ray spectroscopy (EDS) analysis, the Kratos Shimadzu Axis Supra+ instrument was used for X-ray photoelectron spectroscopy (XPS) measurements, and the Agilent 5110 ICP-OES system was used for inductively coupled plasma spectroscopy (ICP-OES) analysis.

[0061] Example 1: Preparation of IrCu4 alloy nanoparticle catalyst

[0062] In the catalyst synthesis process, iridium and copper precursors were dissolved in an appropriate amount of oil solution at a metal atomic molar ratio of 1:4 to obtain a green solution, which was then heated and stirred in an oil bath to obtain IrCu4 alloy nanoparticles.

[0063] 0.05 mmol of iridium precursor acetylacetone and 0.2 mmol of copper precursor acetylacetone, with an atomic molar ratio of iridium to copper of 1:4, were dissolved in 50 mL of oleylamine solution to form a uniform green solution. The solution was then heated and stirred in an oil bath at 260 °C for 5 h at a stirring rate of 500 rpm to obtain IrCu4 alloy nanoparticle catalyst.

[0064] Subsequently, the crystal structure of the catalyst was analyzed using XRD under conditions where the 2θ range was from 10° to 80°. The morphology of the catalyst was observed using TEM at an operating voltage of 200 kV, and the elemental composition of the catalyst was determined by EDS. The XRD results are shown below. Figure 1 As shown, the main peak positions of the catalyst correspond to the characteristic peaks of the IrCu4 alloy. TEM images are shown below. Figure 2 As shown, the nanoparticles are uniformly dispersed with an average particle size of approximately 3.17 nm. The EDS image is shown below. Figure 3 As shown, the atomic contents of Ir and Cu in the obtained IrCu4 alloy are 44.6% and 55.4%, respectively, with atomic ratios of 21.0% and 79.0%. ICP-OES analysis shows that the atomic contents of Ir and Cu are 45.0% and 55.0%, respectively, with atomic ratios of 21.3% and 78.7%. Figure 4 The image shows the 4f energy spectrum of IrCu4 nanoparticles and Ir nanoparticles, while the IrCu4 alloy only shows Ir. 0 The peak indicates that the presence of Cu protects the metallic state of Ir from oxidation by air.

[0065] Electrochemical tests were performed in a standard H-type cell with the catalyst deposited on Vulcan XC-72R carbon black at a metal loading of approximately 5 wt%. The NO3RR was measured using a Corrtest CS310M electrochemical workstation. The concentration was 0.4 mg cm⁻¹. 2 The catalyst loading was determined using carbon paper, an Ag / AgCl electrode (saturated KCl aqueous solution), and a Pt foil as the working electrode, reference electrode, and counter electrode, respectively. The final results showed that the IrCu4 alloy catalyst achieved an onset potential of 0.4 V and a current density of 30 mA cm⁻¹ at approximately 0 V. -2 .

[0066] Under simulated commercial conditions (flow electrolyzer parameters: electrolyzer area 16 cm²), 2 A membrane electrode assembly (MEA) was used, with IrCu4 catalysts at both the cathode and anode. The electrolyte was 1M KOH + 0.1M KNO3. Operating conditions: The electrolyzer operated at 2 mA / cm². 2 (operating at a current density), the catalyst operates stably for 50 hours at a voltage below 1.23V, achieving efficient ammonia generation ( Figure 5 ).

[0067] Comparative Example 1

[0068] Synthesis and Comparison of Single Metal Particle Catalysts and IrCu4 Alloy Nanoparticle Catalysts

[0069] To further verify the beneficial effects of this application, comparative experiments were conducted using single metal catalysts (single iridium catalyst and single copper catalyst) and the same NO3RR test was performed under the same experimental conditions as in Example 1. The results showed that the onset potential of the single iridium catalyst was only about 0.2V, and the current density at 0V was only 6mA cm⁻¹. -2 The reaction activity of a single copper catalyst is almost negligible within the same voltage range. Compared to the IrCu4 alloy catalyst, the single catalyst exhibits lower catalytic activity, which further demonstrates the superiority of the catalyst presented in this application.

[0070] The above description is merely a few embodiments of this application and is not intended to limit this application in any way. Although this application discloses preferred embodiments as described above, it is not intended to limit this application. Any changes or modifications made by those skilled in the art without departing from the scope of the technical solution of this application using the disclosed technical content are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A nanoparticle catalyst, characterized in that, The catalyst has the chemical formula MCu4; where M represents a noble metal, and M is selected from Ir, Pt, and Pd. The atomic ratio of precious metals to copper is 1:

4.

2. The nanoparticle catalyst according to claim 1, characterized in that, The catalyst has an alloy structure, in which copper atoms partially replace the positions of noble metal atoms in the crystal lattice, forming a uniformly distributed alloy phase. The catalyst has a face-centered cubic (FCC) crystal structure.

3. The nanoparticle catalyst according to claim 1, characterized in that, The catalyst has an average particle size of 3 to 3.5 nm.

4. The method for preparing the nanoparticle catalyst according to any one of claims 1 to 3, characterized in that, The preparation method includes: The noble metal precursor and Cu precursor were dissolved in an oil solvent and heated and stirred to obtain the nanoparticle catalyst.

5. The preparation method according to claim 4, characterized in that, The noble metal precursor is selected from at least one of iridium acetylacetonate, chloroplatinic acid, and palladium chloride. The Cu precursor is selected from at least one of copper acetylacetonate and copper chloride.

6. The preparation method according to claim 4, characterized in that, The oil solvent is selected from at least one of oleylamine and octadecene.

7. The preparation method according to claim 4, characterized in that, The molar ratio of the noble metal precursor to the Cu precursor is 1:

4.

8. The preparation method according to claim 4, characterized in that, The ratio of Ir precursor to oil solvent is 1 mg: 2-5 mL.

9. The preparation method according to claim 4, characterized in that, The heating and stirring conditions are: temperature of 200-300℃, time of 3-8h, and stirring speed of 400-600rpm.

10. The application of the nanoparticle catalyst according to any one of claims 1 to 3 in the electroreduction of nitrate to ammonia.